Oral and Topical Insecticide Response Bioassays and Associated Statistical Analyses Used Commonly in Veterinary and Medical Entomology. Issue 6 (2nd November 2020) - Burgess, Edwin R; King, Bethia H; Geden, Christopher J
Abstract: Veterinary and medical entomologists who are involved in research on pest control often need to perform dose–response bioassays and analyze the results. This article is meant as a beginner's guide for doing this and includes instructions for using the free program R for the analyses. The bioassays and analyses are described using previously unpublished data from bioassays on house flies, Musca domestica Linnaeus (Diptera: Muscidae), but can be used on a wide range of pest species. Flies were exposed topically to beta-cyfluthrin, a pyrethroid, or exposed to spinosad or spinetoram in sugar to encourage consumption. LD50 values for beta-cyfluthrin in a susceptible strain were similar regardless of whether mortality was assessed at 24 or 48 h, consistent with it being a relatively quick-acting insecticide. Based on LC50 values, spinetoram was about twice as toxic as spinosad in a susceptible strain, suggesting a benefit to formulating spinetoram for house fly control, although spinetoram was no more toxic than spinosad for a pyrethroid-resistant strain. Results were consistent with previous reports of spinosad exhibiting little cross-resistance. For both spinosad and spinetoram, LC50 values were not greatly different between the pyrethroid-resistant strain and the susceptible strain.